YOUTUBE KIDZ APPLICATION AS A MEDIUM FOR BROADCASTING ISLAMIC EDUCATIONAL CONTENT FOR EARLY CHILDHOOD - Ahmad Fibrianto Ahmad Fibrianto; Muhammad Khoirul Huda; Ahmad Muhammad Diponegoro (Proceeding International Seminar of Islamic Studies, 2023)
The development of an increasingly advanced era followed by increasingly sophisticated technological developments makes an increase in a more creative, imaginative mindset in understanding the development of information media. Interestingly, the various application features available are much liked by children. How would it be if there were no boundaries in seeking information and managing broadcasts through the media that children watch, especially early childhood who are not yet able to sort and choose what is good and what is bad, so that often these shows can become a role models. This study aims to find out how the YouTube Kidz application is a medium for broadcasting Islamic educational content for early childhood. This research method takes the form of library research through tracing various scientific works, in the form of books, papers, journals about media (especially YouTube Kids), then the stages of processing data and analyzing the data that has been collected, the author uses a descriptive analysis method. The results of this study indicate that Islamic content in the YouTube Kidz application includes broadcasts of a series of Islamic children's songs and prayers, Islamic story series and stories which the researcher analyzes as an in-depth study of educational themed content